2012
DOI: 10.1093/ehjci/jes172
|View full text |Cite
|
Sign up to set email alerts
|

Patients with hypertrophic cardiomyopathy at risk for paroxysmal atrial fibrillation: advanced echocardiographic evaluation of the left atrium combined with non-invasive P-wave analysis

Abstract: P-wave duration combined with LA antero-posterior diameter and myocardial deformation indices resulted in a higher power for discriminating HCM-PAF patients, when compared with individual parameters derived from either wavelet analysis or 2D echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
1
9
0
3
Order By: Relevance
“…8,19 Several reports demonstrate that increased LA volume heralds increased risk of AF and might be preferred over LA diameter. 7,8,20,21 The current study confirms this hypothesis, indicating higher sensitivity and negative predictive value of LA volume versus diameter to identify patients at risk for new-onset AF.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…8,19 Several reports demonstrate that increased LA volume heralds increased risk of AF and might be preferred over LA diameter. 7,8,20,21 The current study confirms this hypothesis, indicating higher sensitivity and negative predictive value of LA volume versus diameter to identify patients at risk for new-onset AF.…”
Section: Discussionsupporting
confidence: 83%
“…9 A recent cross-sectional report in a limited number of patients indicated more impaired lateral reservoir Dopplerderived strain (rate) in HCM patients with versus without AF. 21 One study in 50 HCM patients indicated that LA reservoir speckle tracking-derived strain independently predicts occurrence of AF requiring hospitalization (odds ratio, 0.85; 95% . 24 The present study, representing the largest cohort of HCM patients evaluated by LA strain to date, demonstrates higher sensitivity of LA strain compared with LA diameter to predict new-onset AF and confirms its independent predictive value for this end point.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, увеличение ЛП при ГКМП обусловлено первич-ной саркомерной миопатией миокарда предсердий, обструкцией выносящего тракта ЛЖ, повышением жесткости миокарда, митральной регургитацией. При проспективном исследовании 427 больных ГКМП, у 41 из которых в дальнейшем развилась ФП уже после включения в исследование, ФВ ЛП и его конечно-диастолический объем были важными маркерами предрасположенности к ФП [26]. Сре-ди показателей, сочетающихся с ФП, также важны размер и индекс объема ЛП, соотношение Е/Е, от-ражающие наличие и степень диастолической дис-функции [48].…”
Section: на допомогу клініцисту / To Help Cliniciansunclassified
“…Согласно рекомендациям по диагностике и лечению ГКМП европейского общества кардиоло-гов (ESC) от 2014г [9], главными факторами, обуслав-ливающими появление ФП у больных ГКМП, явля-ются повышение давления в полости левого пред-сердия (ЛП) и увеличение его размеров, а также возраст. Рядом авторов установлена взаимосвязь ФП с наличием обструкции выносящего тракта левого желудочка (ВТЛЖ) с митральной регургитации (МР), продолжительностью P-зубца более 140 мсек на сигнал-усредненной ЭКГ, пароксизмами супра-вентрикулярной тахикардии, изменениями сегмента ST на ЭКГ, желудочковой экстрасистолией, отсро-ченным накоплением гадолиния по данным МРТ сердца, снижением резерва коронарного кровотока [9][10][11]. Для выявления эпизодов ФП больным ГКМП рекомендовано 48-часовое мониторирование ЭКГ каждые 6-12 месяцев при диаметре ЛП ≥45 мм (IIaC) [9].…”
Section: оригинальные статьиunclassified